Dante and Rossetti: Translation, Pastiche, Ritual, Fate - McGann, Jerome J. (Hilda Hulme Lecture Series, 2005)
In October 1869, Pre-Raphaelite painter and poet, Gabriel Dante Rossetti exhumed the grave of his former muse and wife, Elizabeth Siddal, to retrieve some earlier poetry he had buried with her. The collection was published as the Poems of D. G. Rossetti in 1870 to great controversy- for their eroticism and hedonism- and none received greater attention than the 'House of Life' sonnets, a ballad intimately describing a romantic relationship. In this short essay, Professor Jerome J. McGann unpacks the origins and inspirations for the 'House of Life' sonnets, including the influence of Italian poet, Dante Alighieri; their shared traits of allegory and theatricality, Rossetti's abstract concepts of life and love, and his many muses. Professor Jerome J. McGann is literary scholar based at the University of Virginia whose work focuses on the history of literature and culture from the late eighteenth century to the present. He has worked extensively at the Rossetti Archives and has been a senior research fellow at the Institute of English Studies, University of London since 1999.